Протиріччя розвитку електронної освіти в освітньо-комунікативному просторі сучасного суспільства - Жовнір, Аліна; Zhovnir, Alina; Жовнир, Алина (Східноєвропейський національний університет імені Лесі Українки, 2020)
У статті висвітлено протиріччя та ускладненості розвитку електронної освіти в сучасному освітньо-комунікативному прос-торі. Представлено розгляд електронної освіти як нової освітньої парадигми XXI ст. Мета статті – огляд та висвітлення ключових форм, завдань, переваг і недоліків електронної освіти як освітньо-комунікативного простору. На основі аналізу наукової літератури запропоновано класифікації й типології електронної освіти за різними критеріями: за ступенем залучення навчальної діяльності до електронного освітнього середовища, за критерієм часу та інституційної регламентації. У роботі наведено функції електронної освіти як соціального інституту, переваги й недоліки цієї освітньої моделі. Неоднозначність оцінок та невизначеність думок стосовно електронної освіти приводить до висновку про, з одного боку, відносну новизну цього феномену в українському освітньому просторі, а з іншого – значні перспективи подальших досліджень і необхідність системного та комплексного вивчення.

The article is devoted to highlighting the contradictions and complexities of the e-learning development in the modern educational and communicative space. The article presents the consideration of e-learning as a new educational paradigm of the XXI century. The aim of the article was to highlight the contradictions in the development of e-learning in the educational and communicative space of modern society based on the analysis of its key forms, tasks, advantages and disadvantages. Based on the analysis of scientific literature, the author proposed classifications and typologies of e-learning based on various criteria: the degree of involvement of educational activities into the e-learning environment, the criterion of time and institutional regulation. The following forms were identified and considered: full cycle e-learning, hybrid education, fragmentary e-learning, «mobile learning», «rapid learning», synchronous and asynchronous e-learning, formal, non-formal and informal education. The article presents the functions of e-learning as a social institution, the advantages and disadvantages of this educational model. Among the key advantages are the following: interactivity, accessibility, flexibility, efficiency and dynamism. The main disadvantages are: technical obstacles, problems of socialization and self-motivation, issues of information security and academic dishonesty, regulatory and legal support of e-learning and others. The ambiguity of assessments and uncertainty of opinions regarding e-learning leads to the conclusion that, on the one hand, the relative novelty of this phenomenon in the Ukrainian educational space, and on the other – significant prospects for further research and the need for systematic and comprehensive study.

В статье рассматривается электронное образование как новая образовательная парадигма XXI в. Цель работы – обзор и освещение ключевых форм, задач, преимуществ и недостатков электронного образования. На основе анализа научной литературы предлагаются классификации и типологии электронного образования на основе различных критериев: по степени включения учебной деятельности в электронную образовательную среду, по критерию времени и институциональной регламентации. В статье приводятся функции электронного образования как социального института, преимущества и недостатки этой образовательной модели. Неоднозначность оценок и неопределенность мнений относительно электронного образования наталкивает на вывод об, с одной стороны, относительной новизне этого феномена в украинском образовательном пространстве, а с другой – о значительных перспективах исследований и необходимости системного и комплексного изучения.
Contradictions in the E-Learning Development in the Educational and Communicative Space of Modern Society
Противоречия развития электронного образования в образовательно-коммуникативном пространстве современного общества
Keywords: електронна освіта; комунікативний простір; дистанційна освіта; електронізація освіти; віртуалізація; e-learning; communicative space; distance education; electronization of education; virtualization; 316.77